Sosialisasi Perencanaan Keuangan Rumah Tangga Dan Menu Makanan Dalam Menghadapi Pandemik Covid-19 - Alfrida V.P. Yamanop; Yensawai E. Rumbiak (UNIVERSITAS CENDERAWASIH, 2021)
COVID-19 pandemic situation that hit the world has disrupted various human activities. The group most vulnerable to the impact of this pandemic is households. Every household is required to be ready to face all risks by managing finances well and fulfilling good nutrition for the family so that the body's immune system can be fulfilled according to government recommendations as an effort to fight Covid-19. To increase knowledge about household financial management and regulate family meal menus, the Socialization of Household Financial Planning in Facing the Covid-19 Pandemic was carried out. The activity was carried out in a group of housewives who live in Hawaii Sentani Koramil Flats Complex, Jayapura district. The activity consists of three activities, namely information on household financial planning, making food menus every week and planting vegetable crops in polybag media. The achievement targets for the participants could be achieved well because of the interest in participating, working on and returning the exercise sheets as well as the addition of simple knowledge on the three activities that have been carried out, namely household financial planning, making food menus and growing vegetables in polybags.